Editorial - Kouis, Dimitris (Journal of Integrated Information Management, 2024)
The first paper presents The University of Thessaly Historical Archive that was used as a paradigm for implementing a new way to deal with complex archival collections. Digital archival items were preserved and enriched with high-quality metadata. The integrated platform implementation resulted in an efficient automated approach to managing the University of Thessaly archives and archival collections, which comprised different digital object formats and included a high volume of digital items, making THE.ME.DO.COM a very successful project example. The second paper presents a survey about the health information behaviour of undergraduate students at the University of West Attica. The survey took place among students of the Department of Archival, Library and Information Studies, where information literacy is taught and in the Department of Physiotherapy, where health subjects are taught. The aim was to discover if any or if both of the above target groups have adopted efficient health information behaviour. The findings are unique in the Hellenic academic environment and lead to the suggestion that information literacy skills should be taught to every Department of the University. The next paper concerns a survey that investigates the causes of teachers’ mental and physical burnout during Covid-19. The survey reveals that the Greek educational system was not adequately prepared to support the educational process, and it suggests that it should improve the mechanisms to support teachers in the performance of their current and future duties. The fourth paper presents digital archival repositories of archival institutions, cultural and information organizations and history research projects. A convergence between research and academic institutions and memory institutions and the development of joint scientific projects is in the interest of the preservation of historical archives, but also of the community to which the stakeholders involved in such projects are addressed.